Study of Political Document Translation from the Perspective of Eco-translatology: Taking the Report on the Work of the Government from 2019 to 2023 as an Example - Li, Jiaying (Transactions on Social Science, Education and Humanities Research, 2024)
In recent years, China has made many breakthrough achievements in all aspects and gradually moved towards the center of the world stage. At the same time, it is particularly important to do a good job in publicity so that more people can clearly understand China’s political stance and characteristic culture. In China, the Report on the Work of the Government is an important way for us to carry out international publicity work, and its English version plays an irreplaceable role in international publicity work. Based on the theory of eco-translatology, this study takes the Chinese and English versions of the Government Work Report from 2019 to 2023 as an example to explore how to show self-confidence in the translation of international publicity represented by political documents and achieve the purpose of cross-cultural communication. It is found that translators often choose translation strategies such as free translation, omitted translation, combined translation and annotation to realize the adaptive choice of translation in three dimensions: language, culture and communication, so as to promote the full communication between the source culture and the target culture and construct a foreign discourse system with Chinese characteristics. This paper aims to enrich the study of political documents from the perspective of the eco-translatology theory, with a view to providing reference for the localization of political documents.